2022
DOI: 10.3390/jcm12010060
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic and Monitoring Biomarkers of Obstructive Sleep Apnea–Umbrella Review of Meta-Analyses

Abstract: Obstructive sleep apnea (OSA) is a prevalent, underdiagnosed disease that imposes a significant impact on the health and wellbeing of patients and a financial burden on individuals, their families, and society. Development of new methods of testing other than an overnight sleep study, such as measurement of serum or plasma biomarkers, may provide an easier diagnostic process to identify patients with OSA and allow earlier initiation of treatment, which might prevent serious comorbidities. We conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…In conclusion, it is important to discover new biomarkers through innovative diagnostic tools [ 134 , 135 ], opening a new translational phase aimed at tuning oxidative profiles in OSAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is important to discover new biomarkers through innovative diagnostic tools [ 134 , 135 ], opening a new translational phase aimed at tuning oxidative profiles in OSAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In sputum only did leptin correlate with fat area, and VEGF level showed a relationship to OSA severity 118 . However, Fiedorczuk et al showed that in OSA patients, blood levels of VEGF and leptin are increased and decrease after continuous positive airway pressure treatment 119 . Katagiri et al found that, in patients with diabetic retinopathy, the vitreous levels of leptin and VEGF are correlated with levels of placental growth factor; they concluded that elevated vitreous levels of VEGF may be linked to severe diabetic retinopathy 120 .…”
Section: Resultsmentioning
confidence: 99%
“…118 However, Fiedorczuk et al showed that in OSA patients, blood levels of VEGF and leptin are increased and decrease after continuous positive airway pressure treatment. 119 Katagiri et al found that, in patients with diabetic retinopathy, the vitreous levels of leptin and VEGF are correlated with levels of placental growth factor; they concluded that elevated vitreous levels of VEGF may be linked to severe diabetic retinopathy. 120 Further, Seung Yang et al found that the logarithm of the intraocular leptin level correlates with the logarithm of serum adiponectin concentration and that level of VEGF in aqueous humor correlates with blood level of adiponectin in diabetic patients with diabetic retinopathy.…”
Section: Human Studiesmentioning
confidence: 99%
“…Recent studies have demonstrated a moderate relationship between elevated levels of in ammatory mediators and OSA, according to the evaluation of plasma or serum samples [11]. Likewise, salivary biomarkers, such as cortisol, are likely predictive of OSA severity [12].…”
Section: Introductionmentioning
confidence: 99%